The Cosmic Sources of Religious Feeling (a possible hypothesis) - Victor F. Petrenko (International Society of Philosophy and Cosmology, 2017)
The article is devoted to the relationship between science and religion, as an important component of human culture and human mentality. The science is considered to have become closely connected with consciousness and is described in the language of rigid formalisms. Religious language is metaphorical and belongs to a "soft" language that is closely related to the images and archetypes of the collective unconscious. In terms of worldview, science and religion are complementary. The values of forms of "religious diversity" of human culture are noted. It is noted that due to ESR phenomenon (or quantum teleportation), it is possible to transfer (it does not concern the information, the possibility of which is limited due to the huge cosmic distances) quantum states in synchrony. It is hypothesized that the source of religious feeling is the cosmic collective unconscious of extraterrestrial civilizations that are ahead of the Earth regarding the origin and affect the Earth's evolution implicitly